Effects of low levels of the antibiotic ciprofloxacin on the polychaete Hediste diversicolor: biochemical and behavioural effects - Nogueira, Ana Filipa (2022)
The release of pharmaceutical chemicals in the biosphere can have unpredictable ecological consequences, and knowledge concerning their putative toxic effects is still scarce. One example of a widely used pharmaceutical that is present in the aquatic environment is ciprofloxacin. Previous indications suggest that this drug may exert several adverse effects on exposed biota, but the characterization of a full ecotoxicological response to this drug is far from complete, especially in estuarine ecosystems. This work aimed to characterize the acute and chronic effects of ciprofloxacin in the polychaete Hediste diversicolor (Annelida: Polychaeta), exposed to environmentally relevant levels of this drug, close to the real concentrations of this pharmaceutical in surface waters. The adopted toxic endpoints were behavioral parameters, combined with a biomarker-based approach (quantification of the activities of catalase (CAT), glutathione-S-transferase (GSTs), cholinesterases (ChEs), glutathione peroxidase (GPx), and lipid peroxidation levels. Exposure to ciprofloxacin caused effects on behavioural traits, such as an increase in burrowing times and hyperactivity, alongside alterations in biomarkers, including a significant increase in CAT activity following acute exposure. In addition, and after both acute and chronic exposure, lipid peroxidation was reduced, while AChE activities were enhanced. It was possible to ascertain the occurrence of pro-oxidative alterations following exposure to low levels of ciprofloxacin, which were counteracted by the triggering of CAT activity. The meaning of the enhancement of AChE activity is not clear, but it appears to be linked with the observed behavioural changes, and may have been associated with the stimulation of the behavioural traits. These data strongly suggest that the presence of ciprofloxacin in estuarine areas is not without risks, and exposed biota, namely polychaete species, are likely to have their ecological roles affected, thereby compromising the chemical, physical and microbiological stability of sediments, which in turn alters nutrient cycles.